Disparities in Quality of Park Play Spaces between Two Cities with Diverse Income and Race/Ethnicity Composition: A Pilot Study - Gavin R. Jenkins (International Journal of Environmental Research and Public Health, 2015)
This study investigated the differences in the quality of park play spaces between an affluent and a non-affluent community in a large US Southeastern metropolitan area. Two cities were purposefully selected to reflect differences in household income and race/ethnicity characteristics. Using the Playable Space Quality Assessment Tool (PSQAT), all parks (n = 11, with six in the affluent city, and five in the non-affluent city) in these two cities were evaluated. The data were analyzed across three aspects of environmental features of the PSQAT: Location, Play Value and Care and Maintenance between parks in the two cities. The Mann-Whitney U test was used to test the study hypotheses. Results indicated significant differences between parks in the two cities in all three aspects of the PSQAT with p-values ≤ 0.03 and effect sizes of > 0.65, suggesting that the affluent city had parks of a higher quality than the non-affluent city. Significant disparity in Play Value (p = 0.009) in parks between these two communities suggests that children and young people are likely to have different experiences of the play spaces in their locality and therefore may experience different physical and psychological health benefits.